Предмет: Математика,
автор: КошкаКамилла
из уравнения (у-х)(х+у)-(у+1)^2=4-(х-1)^2 выразите переменную:
а) х; б) у.
(Попрошу подробное решение)
Ответы
Автор ответа:
0
ху+у² - х²-ху - у² - 2у-1=4-х² +2х - 1
-2у=4+2х
2х+2у= -4
х+у= - 2
х= - 2 -у
у= - 2 - х
-2у=4+2х
2х+2у= -4
х+у= - 2
х= - 2 -у
у= - 2 - х
Похожие вопросы
Предмет: Алгебра,
автор: feridekanybekova05
Предмет: История,
автор: Аноним
Предмет: Физика,
автор: DedLy1337
Предмет: География,
автор: achersiev
Предмет: Литература,
автор: паша115